Candidemia in an Immunocompromised Patient - Jyothi, Lakshmi; Reddy, Naveen P.; Naaz , Shazia (New Horizons in Medicine and Medical Research Vol. 11, 2022)
An immunocompromised patient with a known history of cerebrovascular accident (CVA) with right-sided hemiparesis of long duration, type 2 diabetes mellitus, and hypertension presented with signs of rhabdomyolysis and later acute kidney injury (AKI). He subsequently developed Guillain Barre syndrome. Initially, haemodialysis was followed by plasmapheresis. After haemodialysis, the patient presented with multiple episodes of vomiting and weakness of all limbs. A culture showed growth of Enterococcus faecalis, and on Day 6, a bloodstream infection with Candida kefyr and a urinary tract infection with Enterococcus faecalis was diagnosed. We report a rare case of bloodstream infection due to C. kefyr. The patient recovered and was discharged successfully with continuous follow-up for the next six months.